2008
DOI: 10.1080/13697130701744696
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and severity of vasomotor symptoms among peri- and postmenopausal women in the United States

Abstract: The Menopause Epidemiology Study builds upon existing literature by providing data on daily frequency and severity of vasomotor symptoms. There are many women with frequent and severe vasomotor symptoms who may benefit from treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(119 citation statements)
references
References 29 publications
(30 reference statements)
3
106
0
10
Order By: Relevance
“…59 Although the prevalence of HFs has increased in Japan, however, it is still lower than in most Western populations. 16,27,59 These findings, along with those from other studies, such as SWAN, 10,27,52,60 allude to an important observation that race=ethnicity may not independently explain HF prevalence, as no statistically significant association was found between ethnicity=race and HFs after adjustments for such covariates as lifestyle, BMI, smoking, menopausal status, and health-related quality of life.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…59 Although the prevalence of HFs has increased in Japan, however, it is still lower than in most Western populations. 16,27,59 These findings, along with those from other studies, such as SWAN, 10,27,52,60 allude to an important observation that race=ethnicity may not independently explain HF prevalence, as no statistically significant association was found between ethnicity=race and HFs after adjustments for such covariates as lifestyle, BMI, smoking, menopausal status, and health-related quality of life.…”
mentioning
confidence: 64%
“…As a result of a longitudinal prospective study, Freeman et al 12 reported that the risk of HFs increased throughout the menopausal transition and was greatest in postmenopausal women (odds ratio [OR] 2.87, 95% confidence interval [CI] 1.76-4.67, p < 0.001). In addition, VMS were most strongly related to the late menopausal transition stage in all racial=ethnic groups 10,14,16,17 and nearly as strongly related to postmenopause, even after adjusting for covariates, 10,12,[18][19][20][21][22] as reported in several other published cross-sectional, 10,[16][17][18]20,22 longitudinal prospective, 12,21 and review 14,19 23 Therefore, when performing analysis on factors that affect the incidence or severity of HFs, the nomenclature of the menopausal stages should be introduced along with other covariates in the final multivariate analysis. In summary, the menopausal stages (mainly the menopausal transition and postmenopause) are strongly associated with HFs, but there is still no single menopausal stage that has been identified as the critical time point for experiencing HFs.…”
Section: The Menopausal Stagesmentioning
confidence: 80%
“…This is likely because at baseline women in the SWAN study were required to have had a menstrual period in the past 3 months, suggesting perimenopause, a time when women are more likely to have VMS. 46 The majority of our sample, however, was postmenopausal. Our lower estimate may also reflect our more stringent definition of VMS.…”
Section: Figmentioning
confidence: 99%
“…Analiza wyników doniesień naukowych pozwoliła na sformułowa-nie wniosku, że istnieje grupa objawów, które w okresie okołomenopauzalnym są szczególnie mocno odczuwane przez kobiety, powodują dyskomfort oraz wyraźnie wpływają na kondycję psychofizyczną i działalność społeczno-zawodową kobiet [5][6][7][22][23][24][26][27][28][29][30][31]. Spektrum obejmuje objawy od dyskomfortu aż do stanu wymagającego interwencji lekarskiej.…”
Section: Wynikiunclassified
“…Szacuje się, że objawy wypadowe mogą dotyczyć nawet 75% kobiet w wieku okołomenopauzalnym [5]. Wśród objawów o podłożu somatycznym najczęściej występują uderzenia gorąca [4,[26][27][28][29][30], zaburzenia snu [4,22,23,29,31] i zwiększona potliwość [4,27].…”
Section: Omówienieunclassified